Male choriocarcinoma presenting with intracerebral hemorrhage: a case report and literature review - Chen, Jie; He, Yu; Ao, Junwen; Wang, Zhengshi; Yang, Kuan; Chen, Miao; Zhao, Xing (Frontiers in Oncology, 2025)
Male choriocarcinoma is an extremely rare malignant tumor. It has the characteristics of hidden onset, easy invasion and metastasis. Clinically, when choriocarcinoma is found in a patient, most of the tumor cells have metastasized to distant organs. This case reports a 65-year-old man with choriocarcinoma with two intracerebral hemorrhages as the main symptom. In this case, we consider the origin of intracranial choriocarcinoma to be testicular. We analyzed the clinical data of this patient and summarized the cases of male choriocarcinoma reported in the past, so as to arouse the attention of clinicians.